A Position and Torque Switching Control Method for Robot Collision Safety - Li, Zhi-Jing; Wu, Hai-Bin; Yang, Jian-Ming; Wang, Ming-Hao; Ye, Jin-Hua (International Journal of Automation and Computing, 2018)
With the increasing number of human-robot interaction applications, robot control characteristics and their effects on safety as well as performance should be taken account into the robot control system. In this paper, a position and torque switching control method was proposed to improve the robot safety and performance, when robots and humans work in the same space. The switching control method includes two modes, the position control mode using a proportion-integral (PI) algorithm, and the torque control mode using sliding mode control (SMC) algorithm for eliminating swing. Under the normal condition, the robot works in position control mode for trajectory tracking with quick response. Once the robot and human collide, the robot will switch to torque control mode immediately, and the impact force will be restricted within a safe range. When the robot and human detach, the robot will resume to position control mode automatically. Moreover, for a better performance, the joint torque is detected from direct-current (DC) motor’s current rather than the torque sensor. The experiment results show that the proposed approach is effective and feasible.